Sue & Tai-chan. 1 - Konami, Kanata, 1958- (Kodansha Comics, 2020)
"Sue is an aging housecat who's looking forward to living out her twilight years in peace. But suddenly her human surprises her, and their quiet, happy home is invaded by an interloper, a little black kitten Tai-chan! Sue doesn't have time to cat-sit this mischievous little ball of fluff, but at least he's only visiting for the day. Right ...?"--Page 4 of cover